On the representation of solutions for the theory of generalized thermoelasticity with three phase-lags - Mukhopadhyay S.; Kothari S.; Kumar R. (My University, 2025)
The aim of the present work is to derive the representation of a Galerkin-type solution in the linear theory of generalized thermoelasticity with three phase-lags, recently developed by Roychoudhuri (2007). Firstly, the representation of a Galerkin-type solution of equations of motion is obtained in the form of a theorem. Then, the representation theorem of a Galerkin-type system of equations of steady oscillations is established. Finally, the general solution of the system of homogenous equations of steady oscillation is also presented based on our theorem. © 2010 Springer-Verlag.